2020
DOI: 10.1556/2006.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant posterior superior temporal sulcus functional connectivity and executive dysfunction in adolescents with internet gaming disorder

Abstract: Background and aims The clinical significance of Internet gaming disorder (IGD) is spreading worldwide, but its underlying neural mechanism still remains unclear. Moreover, the prevalence of IGD seems to be the highest in adolescents whose brains are in development. This study investigated the functional connectivity between large-scale intrinsic networks including default mode network, executive control network, and salience network. We hypothesized that adolescents with IGD would demonstrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…FC between AIC and pSTS correlated positively with cognitive problems. These findings indicate that adolescents with PG are at risk for executive dysfunctions and an imbalance between different brain networks 35 …”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…FC between AIC and pSTS correlated positively with cognitive problems. These findings indicate that adolescents with PG are at risk for executive dysfunctions and an imbalance between different brain networks 35 …”
Section: Discussionmentioning
confidence: 72%
“…58 Adolescents with PG showed altered FC of the SN or DMN with the left pSTS. 35 pSTS plays an important role in the social brain network responsible for social cognition or mentalizing processes. PG might increase the connection between SN and social brain network, which is potentially associated with the amount of online social interactions.…”
Section: Local Neural Inefficiency and Network Dysfunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Executive control dysfunction is a common feature in the subjects with PIU ( 39 ). In our study, multiple brain regions are involved in the executive control function of the brain, mainly including STGtp, SFGdl, and MFG.…”
Section: Discussionmentioning
confidence: 99%
“…This results in adolescents becoming extremely aggressive, sad and rebellious. A study conducted by Lee and colleagues 4 involving adolescents with Internet gaming disorder demonstrated that Internet addicts tend to process things much slower than their non-internet addict counterparts.…”
Section: Introductionmentioning
confidence: 99%